The Urgency of English Writing Skills in Copywriting & Digital Marketing - Mardiana, Diand; Suhardianto; Susi Oktafiani; Desi Anggraini (ASIAN PUBLISHER, 2024)
In the digitalization era, English writing skill has a very important role, especially in copywriting and digital marketing. The purpose of the research is to identify the urgency of English writing skill in creating effective content for global audiences. By using qualitative descriptive approach, Data was obtained through deep interviews, documentation studies, observation and questionnaire from digital marketing practitioner, copywriter professional and digital marketing academia. The result of the research shows that the ability of English writing contributing significantly to the success of a marketing strategy such as the increasing engagement and the content attractiveness. The research findings also reveal the main challenges faced by practitioners, including a lack of training, time constraints in content production, and cross-cultural communication barriers. However, opportunities to overcome these challenges are widely available through the implementation of industry-driven training programs, the use of digital tools, and cross-cultural collaboration in producing globally relevant content. These findings highlight the importance of synergy between technical skills and cultural context understanding in optimizing the potential of digital marketing. This research provides both practical and theoretical contributions by recommending strategies to improve English writing skills, whether through formal education or professional training. Furthermore, this study is expected to serve as a reference for educational institutions and industry players in aligning training programs with global market needs.